2021
DOI: 10.3390/su13063034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Green Development Efficiency of the Major Cities in Gansu Province, China

Abstract: Green development (GD) has become a new model of sustainable development across the world. However, our knowledge of green development efficiency (GDE) in Gansu province is poor. In remedy, this study, based on the panel data of 12 major cities in Gansu from 2010 to 2017, employed the super-efficient Slack-based measure (SBM) to analyze and evaluate GDE from the input–output perspective. Furthermore, we analyzed the input redundancy and output deficiency of identified inefficient cities in 2017 and conducted s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 69 publications
(216 reference statements)
0
9
0
Order By: Relevance
“…e index system of green economy, education development, and technological innovation is designed, respectively. First of all, the development of green economy not only includes the growth of the economy scale but also the improvement of the economic structure and the increase of economic efficiency from the reference literature [28][29][30]. 12 indicators such as green GDP (100 million yuan) and gross industrial product above designated size (100 million yuan) were selected to design the indicator system of green economy from these three dimensions which are the scale of economic development, the structure of economic development, and the benefit of economic development.…”
Section: Design Of Index System Of Green Economy Education Development and Technological Innovationmentioning
confidence: 99%
“…e index system of green economy, education development, and technological innovation is designed, respectively. First of all, the development of green economy not only includes the growth of the economy scale but also the improvement of the economic structure and the increase of economic efficiency from the reference literature [28][29][30]. 12 indicators such as green GDP (100 million yuan) and gross industrial product above designated size (100 million yuan) were selected to design the indicator system of green economy from these three dimensions which are the scale of economic development, the structure of economic development, and the benefit of economic development.…”
Section: Design Of Index System Of Green Economy Education Development and Technological Innovationmentioning
confidence: 99%
“…For example, Zhang et al (2015) explained the driving force of government innovation diffusion from the perspective of neo-institutionalism theory and found that the driving force of government innovation diffusion has the characteristics of stages. Liu et al (2021) studied the multi-factor combination path of the comprehensive promotion of LGIS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Only by increasing the support of scientific and technological innovation funds and making it transition to the right end of the "U-shaped" curve can the government facilitates the role of scientific and technological innovation in promoting ecological efficiency. The green development efficiency indicator emphasizes the symbiosis and interaction mechanism of the economic, social, and environmental systems (Liu et al, 2021). Therefore, through data envelopment analysis, this paper uses the Super-SBM model to build a green development-efficiency-index evaluation system, then uses the GMM model to inquire about the relationship between local government innovation support and green development efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Literature [13] used the spatial Durbin model and panel data of Huaihe River economic belt to conduct a study, and found that the environmental regulation shows inverted U on the economic high-quality development of the region, and at the same time, there is a spatial spillover effect of the economic highquality development. Literature [14] based on the panel data of 12 major cities in Gansu province and the slack Measurement (SBM) on the efficiency of green economic development in Gansu, pointed out that the overall GDE in Gansu presents a situation of high east and low west, and concluded that Gansu needs to improve the use of resources and technological innovation, reduce the pollution emissions and optimize the industrial structure, and promote the sustainable development of the green economy. Previous studies have shown that green, low-carbon and circular economy has a positive and significant impact on the development of industrial structure, accompanied by space spillover effect.…”
Section: Introductionmentioning
confidence: 99%